Complete Genome Sequence of an Efficient Rhizobium leguminosarum bv. viciae Strain, A1 - Afonin, Alexey M. (Microbiol Resour Announc, 2020)
Rhizobium leguminosarum strain A1 is used in inoculation experiments with a wide range of pea (Pisum sativum L.) lines. In this study, we report the genome sequence of strain A1, consisting of a 5.06-Mbp circular chromosome and circular plasmids ranging from 804,800 bp to 154,738 bp long.